The Flash Magazine - September 2018 edition - University of Embu (University of Embu, 2018)
In this edition of the Flashlight Magazine, we feature various revolutionary events that have had a tremendous impact internally and externally, which are evident enough that we live true to our philosophy of enhancing human capacity for societal development. One of the main achievements of the University is the development of major infrastructure that would enhance excellent service delivery. These include: a spacious, modern and well equipped Library and Administration Block that will accommodate staff members; and part of it will be used as lecture halls. Another major achievement is the certification to Information Security Management System based on ISO 27001:2013 and recertification to ISO 9001:2015 which validates the University’s unrelenting adherence to best practises and processes. Giving back to society is ethical for any organization. The University of Embu has taken this position seriously and through the efforts of key University personnel, establishment of an endowment fund is underway and its success will see many needy students benefit. What is your part in this as an individual? Each one of us is called upon to support this noble cause. The enthusiasm with which these developments have been received by students, staff and the community is amazing. It’s clear that the University of Embu is committed to quality and excellence at every stage of service delivery. We are all happy to serve and we actually are more than grateful to have the opportunity to do so. We are proud of our students who from this graduation day, turn to graduates with a vantage position. To our graduates, whom we confidently release to the market, we urge you to remain innovative, spread your wings, touch hearts and brighten your corners; for these are the strongholds you have been equipped with through training at the University of Embu.